Developing farm-specific marginal abatement cost curves: Cost-effective greenhouse gas mitigation opportunities in sheep farming systems. (December 2015) - Jones, A.K.; Jones, D.L.; Cross, P.
Highlights: Farm-specific greenhouse gas marginal abatement cost curves (MACCs) are developed. Cost negative abatement potential identified on lowland, upland and hill sheep farms. Productivity and efficiency are influential drivers for emissions abatement on all farms. Individual farm conditions cause heterogeneity in the effectiveness of other measures. Farm-specific MACCs can inform the development of mitigation measure guidelines. Abstract: Growing demand for agricultural produce, coupled with ambitious targets for greenhouse gas emissions reduction present the scientific, policy and agricultural sectors with a substantial mitigation challenge. Identification and implementation of suitable mitigation measures is driven by both the measures' effectiveness and cost of implementation. Marginal abatement cost curves (MACCs) provide a simple graphical representation of the abatement potential and cost-effectiveness of mitigation measures to aid policy decision-making. Accounting for heterogeneity in farm conditions and subsequent abatement potentials in mitigation policy is problematic, and may be aided by the development of tailored MACCs. Robust MACC development is currently lacking for mitigation measures appropriate to sheep systems. This study constructed farm-specific MACCs for a lowland, upland and hill sheep farm in the UK. The stand-alone mitigation potential of six measures was modelled, against real farm baselines, according to assumed impacts on emissions and productivity. The MACCs revealed the potential for negative cost emissions' abatement in the sheep industry. Improving ewe nutrition to increase lamb survival offered considerable abatement potential at a negative cost to the farmers across all farms while, lambing as yearlings offered negative cost abatement potential on lowland and upland farms. The results broadly advocate maximising lamb output from existing inputs on all farm categories, and highlight the importance of productivity and efficiency as influential drivers of emissions abatement in the sector. The abatement potentials and marginal costs of other measures (e.g. reducing mineral fertiliser use and selecting pasture plants bred to minimise dietary nitrogen losses) varied between farms, and this heterogeneity was more frequently attributable to differences in individual farm management than land classification. This has important implications for the high level policy sector as no two farms are likely to benefit from a generic one size fits all approach to mitigation. The construction of further case-study farm MACCs under varying farm conditions is required to define the biophysical and management conditions that each measure is most suited to, generating a more tailored set of sector-specific mitigation parameters.